IMPLEMENTASI GOOGLE APPS UNTUK PENGELOLAAN LABORATORIUM PERIKANAN - Jemi Ferizal; Wahyu Adi; iski zaliman; Siti Aisyah (JUTIM (Jurnal Teknik Informatika Musirawas), 2026)
Manual laboratory management practices commonly found in many educational institutions often create various challenges, such as data duplication, delays in information delivery, recording errors, and ineffective coordination across service units. These issues not only hinder operational efficiency but also reduce service quality, decision-making accuracy, and the laboratory’s ability to respond promptly and appropriately to academic demands. This study designed and implemented a management system for the Marine Fisheries and Hatchery Laboratory based on Google Workspace Tools, including Google Forms, Google Spreadsheets, AppSheet, and Google Sites. The integration of these tools aims to improve work efficiency, information accuracy, and the speed of administrative and laboratory service processes. The study employed the Rapid Application Development (RAD) method, consisting of requirement analysis, system design using UML, prototype development, implementation, and user evaluation. Data were collected through interviews, direct observations, document reviews, and Likert-scale questionnaires. The analysis shows that all evaluation indicators fall within the range of 85–90%, with average scores of 4.26 for effectiveness, 4.23 for efficiency, and 4.36 for user satisfaction, all categorized as very high. The system proved capable of enhancing information accuracy, accelerating service workflows, increasing process transparency, and improving internal coordination. The Rapid Application Development (RAD) method used in this study was found to be more effective than conventional approaches such as Waterfall and Agile, as it enables rapid, iterative, and user-oriented system development. This model is highly suitable for replication as a cloud-based laboratory management solution that is efficient, adaptive, and user-centric.